The Effect of Technological Environment and Product Rivalry on R&D Effort and Licensing of Inventions - Wilson, Robert W. (The Review of Economics and Statistics, 1977)
JN the literature on the macroeconomic aspects of R&D and technical change, several authors have emphasized the importance of technological opportunity as an influence on firms' innovative efforts. Phillips (1966, 1971) has been the leading proponent of a view that exogenous scientific progress is the key determinant of an industry's innovative effort and progressiveness. Scherer (1965) and Comanor (1967) have also used the concept of technological opportunity in their empirical work. The common empirical finding of these three authors is that their measures of technological opportunity exerted a strong positive influence on firms' and industries' R&D efforts. The present paper represents an effort both to extend the knowledge of the influence of opportunity on R&D and also to examine the relation among technological opportunity, R&D effort, and licensing of inventions. A license grants either the legal rights to, or the knowledge of, an invention' to the licensee and may require royalty payments in return. Licensing is a potentially important means of transferring technology2 and is also a strategic variable where firms are engaged in product rivalry based on the physical characteristics of their products. The emphasis of this paper is both conceptual and empirical. The first section below describes a framework for viewing the influence of technological environment on R&D effort and licensing. It is argued that there are two important dimensions of what other authors have referred to as technological opportunity. The second section then tests the implications of the conceptual arguments. Testing of these implications uses new data, collected for this study, on firms' R&D spending and license payments.